THE GEM HIDDEN BEHIND PREDICTABILITY: DISCUSSING EFFICIENCY IN AND OF INVESTMENT ARBITRATION - Rajković, Nataša (Pravni zapisi, 2024)
The paper discusses the status quo regarding efficiency in investment arbitration and suggests how predictability of the arbitral outcome can improve both efficiency in and of investment arbitration. First, the paper will address the cost and duration of investment arbitration. Second, it will look at the provisions of the 2022 ICSID Arbitration and Mediation Rules, as well as UNCITRAL Working Group III Draft Provisions, aimed at increasing efficiency in investment arbitration. Third, it will present efficiency in and of investment arbitration, on the one hand, and predictability, on the other, as intertwined issues. Fourth, it will use the intra-EU jurisdictional objections ratione personae and voluntatis as examples of how the unpredictability of arbitral outcomes reduces the efficiency in and of investment arbitration. Fifth, it will present some of the solutions that could improve efficiency in and of investment arbitration.
Keywords: Investment Arbitration; Efficiency; Predictability; Intra-EU Jurisdictional Objections; Spanish Saga Cases; ICSID; UNCITRAL; Precedent